How to Vote Correctly: An Experimental Study on the Impact of Political Sophistication, Cognitive Load, and Decision-Making Strategies - Kosta Bovan (Anali Hrvatskog Politološkog Društva, 2022)
The concept of correct voting, which refers to a vote that is the same one that would have been made under conditions of full information, has been used to evaluate citizens' voting decisions in various settings. Most studies either focus on determining individual and situational predictors of correct voting or determining the correctness of voting via heuristics. Since heuristics can lead to better decision outcomes than systematic processes, the goal of this study was to analyze how diﬀerent modes of decision-making strategies, as well as individual and situational characteristics, contribute to correct voting. To answer this question, an experiment was conducted in Croatia, a previously unstudied context for correct voting, in which participants gathered information on four parties in a mock election campaign. Results showed that higher political motivation and usage of compensatory decision-making strategies had a positive impact on the probability of casting a correct vote. However, direct eﬀect of cognitive load was found for participants with low levels of political motivation, for which an increase in cognitive load resulted in 25% less probability of voting correctly.